Maternal Pre-Pregnancy Obesity Combined With Abnormal Glucose Metabolism Further Increases Adverse Pregnancy Outcomes in Chinese Pregnant Women - Li, Mei-Fang; Ke, Jiang-Feng; Ma, Li; Wang, Jun-Wei; Zhang, Zhi-Hui; Li, Jing-Bo; Li, Lian-Xi (Frontiers in Endocrinology, 2022)
Aims Our aim was to evaluate the separate and combined effects of maternal pre-pregnancy obesity and gestational abnormal glucose metabolism (GAGM) on adverse perinatal outcomes. Methods A total of 2,796 Chinese pregnant women with singleton delivery were studied, including 257 women with pre-pregnancy obesity alone, 604 with GAGM alone, 190 with both two conditions, and 1,745 with neither pre-pregnancy obesity nor GAGM as control group. The prevalence and risks of adverse pregnancy outcomes were compared among the four groups. Results Compared with the normal group, pregnant women with maternal pre-pregnancy obesity alone, GAGM alone, and both two conditions faced significantly increased risks of pregnancy-induced hypertension (PIH) (odds ratio (OR) 4.045, [95% confidence interval (CI) 2.286–7.156]; 1.993 [1.171–3.393]; 8.495 [4.982–14.485]), preeclampsia (2.649 [1.224–5.735]; 2.129 [1.128–4.017]; 4.643 [2.217–9.727]), cesarean delivery (1.589 [1.212–2.083]; 1.328 [1.095–1.611]; 2.627 [1.908–3.617]), preterm delivery (1.899 [1.205–2.993]; 1.358 [0.937–1.968]; 2.301 [1.423–3.720]), macrosomia (2.449 [1.517–3.954]; 1.966 [1.356–2.851]; 4.576 [2.895–7.233]), and total adverse maternal outcomes (1.762 [1.331–2.332]; 1.365 [1.122–1.659]; 3.228 [2.272–4.587]) and neonatal outcomes (1.951 [1.361–2.798]; 1.547 [1.170–2.046]; 3.557 [2.471–5.122]). Most importantly, there were no obvious risk differences in adverse pregnancy outcomes between maternal pre-pregnancy obesity and GAGM group except PIH, but pregnant women with both obesity and GAGM exhibited dramatically higher risks of adverse pregnancy outcomes than those with each condition alone. Conclusions Maternal pre-pregnancy obesity and GAGM were independently associated with increased risks of adverse pregnancy outcomes. The combination of pre-pregnancy obesity and GAGM further worsens adverse pregnancy outcomes compared with each condition alone.